2014
DOI: 10.1177/0004865814554306
|View full text |Cite
|
Sign up to set email alerts
|

Taking the problem seriously? Sentencing Indigenous and non-Indigenous domestic violence offenders

Abstract: The 'problem' of Indigenous domestic violence has become increasingly dominant in populist and government discourse, with the criminal justice system (including the courts) being criticised for the possible lenient treatment of offenders. Using a population of cases sentenced in New South Wales from January 2009 to June 2012, this paper uses multivariate analyses to explore the intersection between Indigenous status, context of violence (domestic vs. nondomestic) and the imprisonment sentencing decision. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…The odds ratio associated with Indigenous status was found to be 1.37, meaning that all else being equal, the odds of an Indigenous offender receiving a prison sentence were 37% higher than that of a non-Indigenous offender. This finding echoes the results of a similar study carried out in the same year by Jeffries and Bond (2015). They found that the risk of imprisonment for Indigenous offenders was the same, regardless of whether they were convicted of a domestic violence or a non-domestic violence offence.…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…The odds ratio associated with Indigenous status was found to be 1.37, meaning that all else being equal, the odds of an Indigenous offender receiving a prison sentence were 37% higher than that of a non-Indigenous offender. This finding echoes the results of a similar study carried out in the same year by Jeffries and Bond (2015). They found that the risk of imprisonment for Indigenous offenders was the same, regardless of whether they were convicted of a domestic violence or a non-domestic violence offence.…”
Section: Introductionsupporting
confidence: 83%
“…Marginal probabilities of offenders by Indigenous status accounting for interaction effects. in previous research between Snowball andWeatherburn (2006, 2007), on the one hand, and Jeffries and Bond (2015) and Donnelly and Poynton (2015), on the other. Our binomial GEE regression models showed that Indigenous status of the offender had a significant effect on the probability of receiving a prison sentence over a suspended sentence or supervised bond.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations